Hydrodynamic Drivers of the 2013 Marine Heatwave on the North West Shelf of Australia. Issue 3 (5th March 2021) - Maggiorano, Anna; Feng, Ming; Wang, Xiao Hua; Ritchie, Liz; Stark, Clair; Colberg, Frank; Greenwood, Jim
Abstract: The 2012/2013 Ningaloo Niño induced a strong marine heatwave (MHW) event on Australia's North West Shelf (NWS) during the austral summer, starting in December 2012 and peaking in January and February 2013. A high‐resolution regional numerical model based on the Regional Ocean Modeling System (ROMS) was implemented to simulate the variability of the upper ocean temperature and ocean circulation and understand the mechanisms that drive the evolution of the MHW. An upper ocean heat budget was used to quantify the roles of air‐sea heat flux and ocean circulation in the development of extreme temperature anomalies over the continental shelf. Results indicate that during December 2012 an increase of net air‐sea heat flux combined with positive horizontal advective heat flux anomaly led to development of the MHW. During the peak in January‐February 2013 high‐temperature anomalies were maintained by a combination of a decrease in negative heat advection and vertical mixing cooling and a decrease in net air‐sea flux warming. The delayed onset of the 2012–2013 Australian monsoon resulted in alongshore wind anomalies on the NWS which in turn caused the advection and mixing anomalies. Plain Language Summary: During the Australian summer 2012/2013 a marine heatwave (anomalously high‐ocean temperatures) developed on Australia's North West Shelf. The MHW developed during December 2012 and peaked in February 2013. To understand its drivers, an ocean numerical model was implemented for the region to simulate the upper ocean temperatures, ocean circulation and exchanges of heat between the ocean and atmosphere. The results indicate that during December 2012 an increase in the amount of heat received from the atmosphere combined with weaker cool water transport from the south led to development of the MHW. During the MHW peak in January‐February 2013, high temperatures were maintained by weaker currents and a decrease in mixing between the upper ocean and the colder layer underneath. These current and mixing anomalies could have been caused by a delayed start of the Australian monsoon season, which caused weaker winds over the region. Key Points: Warming event on the North West Shelf in austral summer 2012/2013 examined using marine heatwave framework An upper ocean heat budget reveals marine heatwave (MHW) was driven by air‐sea heat flux, horizontal advection, and vertical mixing anomalies Wind anomalies associated with delayed onset of the 2012/2013 Australian monsoon drove the advection and vertical mixing anomalies